Deformation and perforation of sandwich panels with aluminum-foam core at elevated temperatures. (November 2017) - Li, Zhibin; Zheng, Zhijun; Yu, Jilin; Lu, Fangyun
Highlights: Low-velocity impact tests at elevated temperatures were carried out for sandwich panels. Differences of deformation and failure behaviors of sandwich panels under quasi-static and low velocity impact tests were studied at different temperatures. Energy absorption capability of sandwich panels were explored and compared at different temperatures. Dynamic energy enhancement was observed by comparing quasi-static perforations with the impact cases. Effects of several key parameters on the load carrying capacity and energy absorption of the sandwich panels during perforation were discussed. Abstract: Quasi-static perforation and low-velocity impact tests at different temperatures were carried out for sandwich panels with aluminum face sheets and a closed-cell aluminum foam core. The deformation and failure behaviors, load carrying capacity and energy absorption capability of sandwich panels were explored and compared at different temperatures. In the experiments, effects of several key parameters, i.e. soaking time, boundary condition, and geometrical size of the indenter, on the load carrying capacity and energy absorption of the sandwich panels during perforation were discussed. The differences of the perforation behavior of sandwich panels at elevated temperatures under quasi-static and low velocity impact tests were also studied.